10.1016/s1541-9800(11)70476-8 (CrossRef Listing of Deleted DOIs, 2000)
PURPOSE: To extend localized quadratic (LQ) RF encoded spin-echo imaging with acquisition and reconstruction strategies that improve efficiency and artifact robustness, positioning it as a practical alternative to 3D FSE for high-resolution volumetric brain MRI. METHODS: The framework integrates (1) additional gradient-echo readouts for simultaneous T2*w or PDw with T2w without prolonging scan time, (2) an in-plane sampling scheme that distributes arms across shot/trajectory types to maximize k-space coverage and render phase inconsistencies as incoherent residue, (3) sliding-slice encoding to disperse through-plane artifacts, (4) a novel loop-ordering to avoid repeated startup cycles and improve motion robustness, and (5) a hybrid 2D/3D Physics-based Reconstruction with Iterative Model-based Enhancement (spiral-PRIME) performing deblurring, fat-water separation, and 3D wavelet denoising. Healthy-volunteer imaging (3 T) was compared with fully sampled LQ and conventional 3D FSE using peak signal-to-noise ratio, structural similarity index measure, pseudo-replica SNR gain, and qualitative review. RESULTS: Sliding-slice with loop-ordering reduced through-plane artifacts and improved temporal efficiency, while in-plane sampling dispersed trajectory inconsistencies as incoherent noise. Spiral-PRIME suppressed undersampling artifacts and noise while preserving fine structure. Relative to spiral-SENSE, spiral-PRIME achieved consistent T2w SNR gains of ∼30%-40% in WM/GM and substantially higher gains for T2*w, with CNR improvements most pronounced for GM-WM. Despite R ≈ 2.33 undersampling, reconstructions closely matched fully sampled references and delivered quality comparable to or exceeding 3D FSE. CONCLUSION: LQ spin-echo with spiral-PRIME enables efficient, multi-contrast volumetric brain imaging with robust artifact suppression and clinically meaningful SNR/CNR gains, supporting its potential as a practical alternative to 3D FSE.